The author’s methodology of functional exercises as a tool for developing a healthy motor culture - Mahilda, Olena (Педагогічна Академія: наукові записки, 2025)
Modern trends in the field of physical culture and health training indicate a growing need for practical approaches that not only promote physical development but also foster sustainable internal motivation for regular physical activity. The purpose of the article is to study the possibilities of functionally oriented training programs in the formation of correct motivational priorities and a culture of healthy motor activity. The focus is on the trainerʼs professional responsibility and on interdisciplinary interaction with medical professionals to maintain a safe and effective training process, as well as to identify common mistakes in setting physical activity goals. To achieve the goal, the following methods were used: analysis of scientific sources, systematization of many years of practical coaching experience and structural modeling of the authorʼs functional training programs. Results. An evaluative analysis of the motivational attitudes and physical condition of the persons involved in training, as well as the feasibility of integrating medical recommendations for load correction and exercise technique, was conducted. It is shown that beginners in functional training mainly focus on aesthetic results, which leads to false expectations, an inadequate distribution of loads, and an increased risk of injury. The developed authorʼs method includes an assessment of the initial level of training, a motivational and value block, a functional set of exercises, a reflexive and corrective block and interdisciplinary support of the training process. This structure allows for the gradual formation of conscious motivation, safe exercise technique and long-term commitment to regular physical activity among different population groups. Conclusions. The authorʼs method of functionally oriented training programs is an effective tool for fostering a healthy movement culture, combining the coachʼs practical experience, medical expertise, and principles of health care. The implementation of such an approach allows for individualization of the training process, guarantees the safety of loads, stimulates conscious motivation, and contributes to the long-term improvement of the physical condition of various groups of people involved in training.